El aprendizaje cooperativo y el desarrollo socio emocional de las niñas y niños del primer año de educación general básica de las escuelas Santa Catalina y Rumiñahui de la parroquia San Lucas del cantón y provincia de Loja. Periodo 2012-2013. Propuesta alternativa - Bustos Espinosa, Lilia Alexandra (2014)
This present research work is about: COOPERATIVE LEARNING AND SOCIAL-EMOTIONAL DEVELOPMENT WITH THE CHILDREN OF FIRST YEAR OF BASIC GENERAL EDUCATION SANTA CATALINA AND RUMIÑAHUI SCHOOLS OF SAN LUCAS PARISH OF CANTON AND -LOJA PROVINCE. ACADEMIC YEAR 2012-2013. Alternative approaches stands out to be taken into account in the teaching process as a strategy to achieve a better social emotional development of students. The general objective proposed was: To establish the importance of cooperative learning in social-emotional development with children of First Year of Basic General Education in Santa Catalina and Rumiñahui Schools of San Lucas Parish of Canton and Loja Province, during the Academic Year 2012-2013, considering that the cooperative and collaborative learning seeks that students interact with their partners from that interaction increases their learning. It is important to mention that to achieve this, teachers play a vital role as it should lead to students who are responsible for their own learning. To carry out the research was carried out with a population of 55 children and 2 teachers. To develop this research work the following methods were used: scientific, deductive, inductive, descriptive and statistical. To gather the information was used the following techniques and tools: Teacher’s survey and Children’s observation guide. From the results obtained in the survey is inferred that 50% of teachers in schools Santa Catalina and Rumiñahui believes that cooperative learning is found to be the ideal solution to overcome the limitations teachers make their students present. Through the observation guide was evident that 50% of children surveyed have not developed the emotional skills expected so we can conclude that cooperative learning is an important strategy to improve the socio emotional development in students that educated in the schools researched.